1990
DOI: 10.1046/j.1537-2995.1990.30790385519.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in vivo hemolysis and the amount of red cell‐bound IgG measured by flow cytometry

Abstract: A flow cytometry method was used to compare the amount of red cell (RBC)-bound IgG in 73 patients with and without immune hemolytic anemia (IHA). The positive results in 10 of the direct antiglobulin tests (DATs) were idiopathic, and those in 25 were due to methyldopa therapy; 38 of the 73 DAT-positive patients were babies born to women with IgG alloantibodies of potential clinical significance. Normal blood donors with (n = 30) and without (n = 121) positive DATs were also tested. RBCs that had been strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 9 publications
2
59
0
4
Order By: Relevance
“…With two exceptions, the results of van der Meulen et al [4] indicated that there was a distinct difference in the number of RBC-bound IgG1 molecules in patients with and without IHA. Garratty and Nance [5] later studied 103 DAT-positive patients and blood donors with and without IHA, but were unable to confirm the distinct difference seen by van der Meulen et al [4]. Using FITC antiIgG to study the RBCs, Garratty and Nance [5] were able to show that, although the mean percentage of cells with increased fluorescence was higher in the group with IHA, there was considerable overlap in the results from both groups (with and without IHA).…”
Section: Detection and Quantitation Of Globulins Red Blood Cell-boundmentioning
confidence: 92%
“…With two exceptions, the results of van der Meulen et al [4] indicated that there was a distinct difference in the number of RBC-bound IgG1 molecules in patients with and without IHA. Garratty and Nance [5] later studied 103 DAT-positive patients and blood donors with and without IHA, but were unable to confirm the distinct difference seen by van der Meulen et al [4]. Using FITC antiIgG to study the RBCs, Garratty and Nance [5] were able to show that, although the mean percentage of cells with increased fluorescence was higher in the group with IHA, there was considerable overlap in the results from both groups (with and without IHA).…”
Section: Detection and Quantitation Of Globulins Red Blood Cell-boundmentioning
confidence: 92%
“…It allows the selective quantitation of immunoglobulin subtypes [1]. However, the practical importance of this enhanced precision is controversial [16], because the correlation of disease severity and red blood cell-bound immunoglobulin is limited.…”
Section: Quantitation Of Red Blood Cell-bound Immunoglobulinmentioning
confidence: 99%
“…Flow cytometry (FC) has been previously utilized for antibody detection, including the detection of red cell autoantibodies (4,5), HLA alloantibodies (6,7), platelet crossmatching (8)(9)(10), and other immmunohematological applications (11,12). Recently, FC was also introduced for the screening of antibodies to red cells for automation by Roback et al (3,13).…”
Section: Introductionmentioning
confidence: 99%